PENGARUH INTENSITAS SCREENTIME DAN KUALITAS KONTEN TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI (3–6 TAHUN) - Arsyla Ma’rifatul Aida Akbar; Nurul Shofiah; Fina Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing use of digital media among young children has raised concerns regarding its relationship with language development. This study aimed to analyze the effects of screen time intensity and content quality on the language development of children aged 3–6 years. A quantitative approach with a regression design was employed. The participants were 212 parents or caregivers of children aged 3–6 years who were selected using purposive sampling. Data were collected through an online questionnaire measuring screen time intensity, content quality, and children's language development. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. The results showed that screen time intensity significantly affected children's language development (β = 0.148; p = 0.014). Content quality also had a significant effect on language development, with a larger standardized coefficient (β = 0.490; p < 0.001). Simultaneously, screen time intensity and content quality significantly affected children's language development (F = 43.782; p < 0.001). The R² value of 0.295 indicated that the two variables jointly explained 29.5% of the variance in children's language development, while the remaining 70.5% was explained by other factors outside the research model. These findings indicate that children's language development is associated not only with the intensity of digital media use but also with the quality of the content accessed. Content quality showed a relatively greater contribution than screen time intensity, indicating the importance of selecting age-appropriate content that supports children's developmental needs when using digital media.